2022
DOI: 10.1039/d2lc00307d
|View full text |Cite
|
Sign up to set email alerts
|

Liver organ-on-chip models for toxicity studies and risk assessment

Abstract: The liver is a key organ that plays a pivotal role in metabolism and ensures a variety of functions in the body, including homeostasis, synthesis of essential components, nutrient storage,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 221 publications
0
25
0
Order By: Relevance
“…Reconstructing an in vitro liver model that mimics in vivo conditions is very challenging and aims to maintain the morphological characteristics and cellular functions of hepatocytes over long periods of culture. In past decades, different liver models based on one or more advanced technologies, such as OoC, 3D spheroids and cells embedded in hydroscaffolds, have been developed [ 17 , 20 , 61 ]. However, to our knowledge, only a few studies have focused on integrating a hydrogel/hydroscaffold into the biochip and there is no system describing a dynamic liver-on-chip model making hepatocyte cultures possible in spheroids, embedded into a hydroscaffold that closely mimics the liver’s ECM.…”
Section: Discussionmentioning
confidence: 99%
“…Reconstructing an in vitro liver model that mimics in vivo conditions is very challenging and aims to maintain the morphological characteristics and cellular functions of hepatocytes over long periods of culture. In past decades, different liver models based on one or more advanced technologies, such as OoC, 3D spheroids and cells embedded in hydroscaffolds, have been developed [ 17 , 20 , 61 ]. However, to our knowledge, only a few studies have focused on integrating a hydrogel/hydroscaffold into the biochip and there is no system describing a dynamic liver-on-chip model making hepatocyte cultures possible in spheroids, embedded into a hydroscaffold that closely mimics the liver’s ECM.…”
Section: Discussionmentioning
confidence: 99%
“…These improvements have shown that liver-centric devices can predict clearance, toxicity, and mechanism of action of certain pharmaceutical compounds to a considerable degree [ 21 , 61 ]. Although liver microphysiological systems have shown great success in predicting the kinetics of selective drugs, their utility in predicting the kinetics of environmental compounds remains largely unexplored [ 23 , 62 , 63 ]. Compared to pharmaceuticals, environmental compounds have a much wider range of physicochemical properties, which have a direct impact on biokinetics [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the last decades, multiple approaches based on tissue engineering and microtechnology have been used to develop relevant in vitro models for animal experiments replacement. Thanks to the progress in microfabrication, microfluidic and bioprinting, OoC technology has emerged as a promising tool to recapitulate in vitro the physiological in vivo environment of the cells or tissues [ 2 , 20 ]. Since the beginnings of microfluidics, PDMS has been the most commonly used material for microfluidics and OoC devices and is still today a widely used material in literature [ 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The liver performs a great number of tasks to support other organs and impacts all physiological system. It is involved in several essential functions including detoxification, protein synthesis and metabolism, glycogen storage, bile secretion, as well as the removal of pathogens and exogenous antigens form the systemic circulation [ 1 , 2 ]. As the major site of xenobiotic metabolism, the liver is exposed to a wide range of exogenous substances and is often the subject of chemical-induced toxicity [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation